PEMANFAATAN TEKHNOLOGI DALAM UPAYA MENINGKATKAN PRODUKTIVITAS USAHA KECIL - Intan Shaferi; Alisa Tri Nawarini; Meutia Karunia Dewi (Performance: Jurnal Personalia, Financial, Operasional, Marketing dan Sistem Informasi, 2016)
Small medium enterprises seems to have change for a better production with their quality and quantity. Still we have SMEs that using traditional method to produce their product. That means unoptimal production because of limitation of time and some unexpected failure that may happened during production. So that, by using touch of technology, will minimizing the failure, effectiving time, and incrasing units of production.